Tronchuda cabbage flavonoids uptake by Pieris brassicae - Ferreres, Frederico (2007)
The flavonoid pattern of larvae of cabbage white butterfly (Pieris brassicae L.; Lepidoptera: Pieridae) reared on the leaves of tronchuda cabbage was analysed by HPLC-DAD-MS/MS-ESI. Twenty flavonoids were identified or characterised, namely 16 kaempferol and four quercetin derivatives. Kaempferol 3-O-sophoroside, a minor component of tronchuda cabbage, was found to be the main component in P. brassicae (15.8%). Apart from this, only two other flavonoids present in significant amounts in tronchuda cabbage (kaempferol 3-O-sophoroside-7-O-glucoside and kaempferol 3-O-sophoroside-7-O-sophoroside) were found in the larvae. The larvae have high amounts of quercetin derivatives (18.5%), which were present only in trace amounts in tronchuda cabbage extracts, suggesting that P. brassicae is able to selectively sequester these flavonoids. The occurrence of a high content of flavonoids not detectable in tronchuda cabbage extracts indicates that P. brassicae larvae are able to metabolize dietary flavonoids.